Behavioral Disorders in Mares with Ovarian Disorders, Outcome after Laparoscopic Ovariectomy: A Case Series - Paola Straticò; Jasmine Hattab; Giulia Guerri; Augusto Carluccio; Lorenza Bandera; Gianluca Celani; Giuseppe Marruchella; Vincenzo Varasano; Lucio Petrizzi (Veterinary Sciences, 2023)
Owner complaints of estrus-related behavior in mares are a common cause of referral for laparoscopic ovariectomy. Granulosa cell tumors are a common neoplastic condition affecting the equine ovary, causing behavioral changes at rest and reduced performance. The reported success rate of ovariectomy in treating behavioral disorders is 64–86%. The aim of this study was to retrospectively evaluate the long-term follow-up of laparoscopic ovariectomy in mares in our case series, focusing on the owner’s perspective of the behavior of the mares after surgery. In addition, the histopathological features of the removed ovaries were investigated. The clinical records of mares that underwent laparoscopic ovariectomy between 2015 and 2022 were retrospectively reviewed. Owners complaining of poor behavior were interviewed about the main behavioral problem leading to referral and its eventual resolution after surgery. Eleven mares were included. The most common complaints were increased sensitivity on both flanks (10/11, 91%) and general riding problems (9/11, 82%). In 5/11 cases (45%), both ovaries were removed by laparoscopic ovariectomy. Histopathologic findings consistent with GCT/GTCT were found in five out of six examined ovaries (five granulosa theca cell tumors, GTCT). According to owner interviews, the scores assigned to each behavior improved significantly after surgery, regardless of histological findings. Although many factors can influence the behavior of horses, granulosa cell tumors (GCTs) proved to be a common cause and, as reported by the owners, ovariectomy resulted in improvement or complete resolution of the abnormal behavior.